Who Wants to Be a Slave? The Technocratic Convergence of Humans and Data - Broudy, Daniel; Arakaki, Makoto (Frontiers in Communication, 2020)
Marshall McLuhan observed in the 1960s that humans are toolmakers whose tools eventually reshape them. Fifty years hence, we suggest that the aphorism should include ‘rewire’ humans as the present age of the internet serves as the global nervous system for humankind. This article explores how, in this present period of the Information Age, media manipulate public opinion about and consent for new digital tools and techniques threatening human agency and sovereignty. This essay introduces the concept of convergence as developed by Henry Jenkins and explores how the practice has expanded in the current global pandemic milieu wherein the interests of a technocratic elite converge to cultivate a general acceptance of the digital tools of a new socioeconomic order. Alongside this analysis stands the historical development of computing tools and the development of data as tools of social control. In a world where the manufactured need for ever-increasing speed and efficiency have largely co-opted human reason, we analyze how digital tools threaten to merge with humans. Enlisted in the effort to examine the integration propaganda are historical accounts of this emerging order as elaborated by key public servants and intellectuals of the 20th century. The primary aim is to situate the top-down attempt to acquire control over the masses in a larger historical context when sophisticated computing tools began serving the need to track and control populations. The essay is an effort to grapple with the complex historical attempt to wield control over people through public relations and technologies.